EFFECT OF HARDENING CONDITIONS ON ALUMINUM ALLOY MICROSTRUCTURE - Demiroren, Hulya (Springer, 2012)
The microstructure of cast alloy Al - 8.88% Si - 3.38% Cu is studied after isothermal hardening at 65 degrees C for 1 - 90 min using light microscopy, X-radiography, and a scanning electron microscope with energy dispersion analysis. After isothermal hardening alloy is aged at 525 degrees C. The duration of isothermal exposure is established in order to obtain high alloy hardness.
Keywords: aluminum alloys; treatment for solid solution; hardening; hardness